Towards a heterogeneous query language for mathematical knowledge - Bercic, Katja; Kohlhase, Michael; Rabe, Florian (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2020)
With more than 120.000 articles published annually in mathematical journals alone, mathematical search has often been touted as a killer application of computer-supported mathematics. But the artefacts of mathematics – e.g. mathematical documents, formulas, examples, algorithms, concrete data sets, or semantic web-style graph abstractions – that should be searched cover a variety of aspects. All are organized in complex ways and offer distinct challenges and techniques for search. Existing representation languages, the corresponding query languages and search systems usually concentrate on only one of these aspects. As a consequence, each system only partially covers the information retrieval needs of mathematical practitioners, and integrated solutions allowing multi-aspect queries are rare and basic. We present an architecture for a generic multi-aspect search system and analyze the requirements on paradigmatic practical information retrieval needs.
CRIS-Team Scopus Importer:2020-11-06